Pengelolaan Ruang Bawah Tanah Dalam Reformasi Hukum Pertanahan Di Indonesia - Nur Nafa Maulida Atlanta; Bayu Dwi Anggono; Fendi Setyawan (Syntax Idea, 2022)
The difficulty of obtaining or using the earth's surface in urban areas has resulted in people starting to look for a number of plots of land below the earth's surface. Thus, a development breakthrough innovation is needed that can address the development of community needs, namely the space below the earth's surface. The use of basements, namely UUPA, automatically refers to property rights in discussing the use of basements. The aim is to find a system for granting land rights or management rights to basements in Law Number 5 of 1960 concerning Basic Agrarian Regulations and Law Number 11 of 2022 concerning Job Creation for individuals. This research is a normative juridical research with collection techniques from the literature which consists of primary and secondary legal materials. The results of this study are the system of granting land rights or management rights to basements in the BAL by basing it on the provisions of Article 2 paragraph (2) of the BAL, the term "management" and "organizes". The Job Creation Law is for individuals or legal entities that are given HGB and HP for a period of time as contained in the concept of basement management in Article 146 paragraph (1) to (5) of the UUCK, namely paragraph (1) The land or space formed in the upper room or underground and used for certain activities can be given HGB, HP, or HPL. In conclusion, the State Authority relates to (a) the use and/or allotment, supply and maintenance of the earth, air, space and natural resources in the territory of the Republic of Indonesia; (b) payment or arrangement of types of land rights; (c) paying or arranging several legal relations between people and legal entities with land as objects.